EMOTIONAL BRANDING PEMBELIAN SEPEDA LIPAT DI ERA COVID-19 - Nandang Bekti Karnowati; Erna Handayani (Value : Jurnal Manajemen dan Akuntansi, 2021)
Abstract The Indonesian phenomenon that has emerged in the current Covid-19 pandemic era is the increasing popularity and high public interest in buying folding bikes. Price released a research analysis of search inetrest for folding bicycles in Indonesia from March to June, wich recorded an increase of up to 900%. This study aims to determine the factors that influence purchasing folding bikes during the Covid-19 pandemic and the role of emotional branding as a mediation factor of consumer behaviour towards purchasing decisions. This study used a purposive sampling technique with 100 respondents who purchased folding bikes during the Covid-19 pandemic from March to September 2020. The quesionnaire data was processed using Partial Least Square (PLS) analysis by testing outer and inner models with path coefficients. The result of the analysis show that psychological factors have a significant positive effect on purchasing decisions. Personal factors, sosial factors and cultural factors do not effect purchasing decisions. Emotional branding does not mediate these factors on purchasing decisions. Keywords: Emotional branding, Consumer Behavior, Purchasing Decisions, Covid-19 Era